EFFECT OF ASPERGILLUS NIGER TREATED FIBRE FEEDSTUFFS ON GROWTH PERFORMANCE AND CARCASS CHOLESTEROL OF GROWING PIGS - AFENI, M. O.; ADEYEMI, M. A.; OGUNDEJI, S. T.; AKINFALA, E. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2024)
The study evaluated copper and zinc availability from Aspergillus niger fermented fibre feedstuffs for effects on growth and carcass cholesterol of growing pigs. Three fibre feedstuffs (Wheat Bran (WB), Brewer Spent Grain (BSG) and Palm Kernel Cake (PKC) were prepared by solid-state fermentation with A. niger to determine bioavailability of copper(Cu) and zinc (Zn). Growth trial was conducted using thirty-six growing pigs with average initial weight of 25.0 ± 0.52 kg, randomly assigned to six dietary treatments in a 3 x 2 factorial experiment of three fibre sources (WB, BSG and PKC) with or without A. niger treatment in a 63 d experiment. The diets were formulated to contain treated and untreated fibre feedstuffs at 30% inclusion level. The results showed that treatment of the fibre feedstuffs with A. niger increased Zn availability in WB, BSG and PKC by 53.35%, 7.90% and 4.54% respectively while copper availability increased by 60.94% and 16.40% in WB and PKC but depressed availability (-1.70%) in BSG treated feedstuff. The growth response showed no significant difference (P >0.05) but the average total cholesterol in pigs fed the diets appeared to decrease significantly (p<0.05) across treatment groups. These values varied between 32.00 mg/100g and 45.56 mg/100g for pigs fed A. niger treated wheat bran and untreated PKC diets respectively. The findings of this study showed that A. niger improved the composition of Cu and Zn, and pigs fed treated BSG diet had the fastest growth while those fed treated PKC diet produced better carcass cholesterol content.